2017
DOI: 10.1111/lam.12742
|View full text |Cite
|
Sign up to set email alerts
|

Internalization ofEscherichia coliO157:H7gfp+ in rocket and Swiss chard baby leaves as affected by abiotic and biotic damage

Abstract: Contamination of leafy vegetables with Escherichia coli O157:H7 is a growing problem, as reported outbreaks are increasing. However, establishment of this human pathogen in the phyllosphere is not completely understood. Using laser scanning confocal microscopy, we demonstrated that E. coli O157:H7gfp+ can invade plant tissue of Swiss chard and wild rocket leaves and that the bacterium is more sensitive to surface sanitization of Swiss chard leaves. Damage to leaf tissue promoted leaf invasion, but the nature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Presence of wild animals and instances of plant damage by equipment used in the field or by weather events should also be considered. Plant damage can provide potential entry points for internalization of human enteric pathogens (Brandl, 2008; Hartmann et al, 2017). In summary, plant damage can occur at all stages of the production chain, both in the field and in processing and distribution, and it is important to minimize such damage in order to maintain high quality throughout the food chain.…”
Section: Potential Hurdlesmentioning
confidence: 99%
“…Presence of wild animals and instances of plant damage by equipment used in the field or by weather events should also be considered. Plant damage can provide potential entry points for internalization of human enteric pathogens (Brandl, 2008; Hartmann et al, 2017). In summary, plant damage can occur at all stages of the production chain, both in the field and in processing and distribution, and it is important to minimize such damage in order to maintain high quality throughout the food chain.…”
Section: Potential Hurdlesmentioning
confidence: 99%
“…These microorganisms can be found both inside and outside parts of the plant tissue. Since bacterial pathogens lack enzymes to degrade cuticle and cell wall of plants, internalization inside the plant tissue occurs through the natural openings, cracked trichomes and damages occurred biotically or abiotically (Burnett and Beuchat, 2001;Hartmann et al, 2017). Natural openings found on the plant, such as hydathodes, stomata, nectarthodes and lenticels, are perfect sites for bacterial penetration.…”
Section: Sem Imagesmentioning
confidence: 99%
“…Seeds and plants are epi-and endophytically colonized by microorganisms (Golberg et al, 2011;Hartmann et al, 2017a;Hirneisen et al, 2012;Hora et al, 2005;Wright et al, 2013) and the individual plants appear to influence their associated microbial community structure, they select specific microorganisms to colonize their tissues (Rosberg et al, 2014), a feature that may not be influenced by management practices. An ongoing argument of whether microorganisms like human enteric pathogens which are not commonly grouped as plant colonizers, end up on plants by accident or if the different plant cultivars might actually be more or less conducive to supporting growth of human pathogens (Teplitski et al, 2009).…”
Section: Plant Colonizationmentioning
confidence: 99%
“…Using high and low risk scenarios for water reservoirs, irrigation techniques, mulching and fertilization. Hartmann et al (2017a) concluded that season, plant species and age rather than cultural management decide the natural colonization of human pathogens in organically grown leafy vegetables. Their results were also confirmed in a greenhouse experiment using untreated chicken manure and pig hair pellets where a gfp-tagged strain of E. coli O157:H7 was supplemented.…”
Section: Risk Scenariosmentioning
confidence: 99%